Recent advances in sustainable drying of agricultural produce: A review. (1st January 2019) - Lamidi, Rasaq. O.; Jiang, L.; Pathare, Pankaj B.; Wang, Y.D.; Roskilly, A.P.
Highlights: A review of the sustainable drying of agricultural products is presented and detailed. Hybrid drying systems are promising and competitive when compared with others. Modelling software that integrates energy source plays a significant role in hybrid system optimisation. Biomass powered CHP system may be a good solution to sustainable food drying in rural areas. Abstract: Quests for sustainability, food security and need to decouple food prices from fluctuating prices of finite fossil fuels are the drivers to sustainable processing and storage of agricultural products. Farming predominantly takes place in rural areas where conventional energy technologies may either be expensive or sometimes technically infeasible to be obtained. This necessitates deployments of renewable energy technologies to remote areas for sustainable power generation, cooling and drying of agricultural product. Renewable systems e.g. solar dryers, solar hybrid dryers, combined power and drying system take leading roles in sustainable drying of farm produce. A number of research studies have been carried out in the past one decade, which mainly concentrate on modelling, simulation and experiment of different sustainable drying techniques. Therefore, this paper aims to present a state of the art review on the contributions of combined power and drying, application of phase change materials and hybrid drying systems with regard to agricultural products. Based on this comprehensive summarization, it is indicated that deployment of biomass powered combined heat and power systems might be a good solution to post-harvest wastes since both electricity and heat for drying of agricultural products can be simultaneously obtained.